32.7k views
1 vote
Combine the like terms to create an equivalent expression:

−4p+(−6p)

2 Answers

2 votes

THE ANSWER IS -10P.

Explanation:

USING BY MULTIPLICATION RULE.

minus × plus = minus

then minus × minus = plus.

so we add the 4p+6p= -10p.

why -10p is come it means THE BIGGER NUMBER SIGN IS MINUS. So it's comes -10p.

HOPE IT HELP......

User Hezbullah Shah
by
4.6k points
4 votes


\huge\text{Hey there!}



\mathsf{-4p + (-6p)}\\\\\mathsf{= -4p - 6p}\\\\\large\text{COMBINE the LIKE TERMS:}\\\\\mathsf{= (-4p - 6p)}\\\\\mathsf{= -4p - 6p}\\\\\mathsf{-10p}\\\\\\\huge\textbf{Therefore, your answer should be:}\\\huge\boxed{\mathsf{-10p}}\huge\checkmark



\huge\text{Good luck on your assignment \& enjoy your day!}



~
\frak{Amphitrite1040:)}

User Ferry To
by
4.6k points